Comparative analysis of 23Na T1 and T2* relaxation times in healthy muscle tissue at 3 and 7 T - Nour Zeitouni; Laurent Ruck; Lena V. Gast; Michael Uder; Arnd Dörfler; Armin M. Nagel; Teresa Gerhalter (Magnetic Resonance Materials in Physics, Biology and Medicine, 2026)
Abstract Objective While most sodium ( 23 Na) MRI studies focus on apparent tissue sodium concentration (aTSC), longitudinal (T₁) and transverse (T₂*) relaxation times may provide additional microstructural and physiological information. This study aimed to establish reference values for 23 Na T₁ and bi-exponential T₂* in human lower-leg muscle at 3 T and 7 T, evaluate methodological factors influencing T₂* quantification, and assess the reproducibility of aTSC. Methods Twenty healthy volunteers underwent 23 Na MRI of the lower leg at 3 T and 7 T using 3D stack-of-stars UTE acquisitions. T₂* was quantified from multi-echo data using bi-exponential fitting with both fixed and free short-component fractions. T₁ was measured with a saturation-recovery approach. aTSC was calculated using calibration phantoms. Results T₁ increased with field strength (3 T 26.5 ± 2.0 ms; 7 T 28.1 ± 1.7 ms), while long T₂* decreased (3 T T₂ l * 20.5 ± 2.9 ms; 7 T T₂ l * 18.4 ± 2.5 ms). T₂* estimation depended on echo sampling and fitting assumptions. Mean aTSC was 17.5 ± 1.7 mM at 3 T and 18.5 ± 1.7 mM at 7 T, with a reproducibility coefficient of variation of 4.1%. Moderate positive correlations between field strengths were observed for short T₂*, its fraction, T₁, and aTSC. Conclusions This study provides reference values for sodium T₁ and bi-exponential T₂* relaxation in human skeletal muscle at 3 T and 7 T and demonstrates high reproducibility of aTSC across field strengths.